La comunicación de padres de familia y su influencia en el desarrollo afectivo de los niños y niñas del nivel inicial del centro educativo “San Francisco” de la comunidad de Gera perteneciente a la parroquia y cantón Saraguro provincia de Loja año lectivo 2012-2013 - Puglla Sarango, José Samuel (2014)
This thesis mentioned above: COMMUNICATION OF PARENTS AND THEIR INFLUENCE ON THE EMOTIONAL DEVELOPMENT OF CHILDREN OF INITIAL LEVEL OF SCHOOLS "SAN FRANCISCO" GERA COMMUNITY OF BELONGING TO THE PARISH AND CANTON SARAGURO Loja Province SCHOOL YEAR 2012-2013. general objective was plotted sensitize parents to the importance of communication and its influence on the emotional development of children's initial level of San Francisco school community of the parish Gera and Canton Saraguro Loja Province, 2012-2013. This subject is of high incidence in children of the community, for this reason in this work prioritized to encourage, motivate parents in the home are communicative, cultivating in their children the values of respect, cementing their children must have good relations with the community, both communication and affection are two significant values that cannot be separated because it depends on the happiness and harmony within the family which is reflected in the daily living and maintaining community harmony each family. For compliance arose methods: scientific, empirical, deductive, hypothetical deductive, analytical synthetic addition to collecting information used instruments such as the survey of 15 parents, one teacher and 15 children was conducted an interview, to complete the investigation work leads to the following conclusion, which is set out below: 60% of parents do not talk at home with their children so these children show affection and socialization problems. In others, 100% of children are not participatory and unsociable because the family did not generate spaces for dialogue and show little affection with him.